Generating random samples from Pareto Distribution to computing the methods to estimating the parameters by simulation - Arif, Ali . L . (University of Thi-Qar Journal, 2019)
In this paper, we carry out a comparison between some estimating methods for the two parameters of Paerto distribution like least squares, moment, ridge regression, relative least squares and maximum likelihood by using the Mean squared errors and total deviation to determine the best method by using different values for the parameters and different sample size. Were generated with use programming simulation by Quick basic